Letter from the Editor-in-Chief - Chicheł, Adam (Journal of Contemporary Brachytherapy, 2021)
Despite the pandemic, it worked and happened! The postponed World Congress of Brachytherapy 2021 finally took place in an online form. I warmly thank Bradley Peters and the whole not listed here team of supporters. Teamwork focusing on a common goal is always fruitful. The GEC-ESTRO Group, in close collaboration with the American Brachytherapy Society (ABS) and supported by the Australasian Brachytherapy Group (ABG), the Asociación Ibero Latinoamericana de Terapia Radiante Oncológica (ALATRO), the Canadian Brachytherapy Group (CBG), the Federation of Asian Organizations for Radiation Oncology (FARO), and  the Indian Brachytherapy Society (IBS) achieved the impossible. We met in one virtual space, discussed many intriguing topics, and challenging research results. Long live brachytherapy!